Pelatihan Penguatan Kapasitas UMKM dan Pelaku Usaha Pariwisata Kota Bandar Lampung melalui Strategi Pemasaran Digital: Pengabdian - Muhammad Saputra; Ita Fionita; Riri Carissa; LisLindawati LisLindawati; Novita Sari; Sri Rahayu (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The development of digital technology and changes in consumer behavior require business actors to adapt through the strategic utilization of digital media. This community service activity aims to strengthen the capacity of micro, small, and medium enterprises (MSMEs) and tourism business actors in Bandar Lampung City in designing and implementing well-planned, market-oriented digital marketing strategies. The implementation method adopts a participatory approach that combines the delivery of conceptual materials, hands-on practice, and mentoring, beginning with the identification of partners’ needs through observation and discussions. The results indicate an improvement in participants’ understanding of digital marketing concepts, content planning, and the selection of appropriate digital channels aligned with business characteristics, accompanied by a shift in mindset from fragmented marketing practices toward more systematic and sustainable marketing strategies. This activity contributes significantly to enhancing the readiness of MSMEs and tourism business actors to compete in the digital era while supporting local economic development and sustainable tourism in Bandar Lampung City.